2009
DOI: 10.1387/ijdb.072417cl
|View full text |Cite
|
Sign up to set email alerts
|

Movement and commitment of primitive streak precardiac cells during cardiogenesis

Abstract: Fate maps are required to address questions about the commitment and differentiation of precardiac cells. Here, we report a detailed study of the precardiac cells located at the level of the primitive streak, employing different experiments with a variety of techniques combining double transplantations, microinjections and immunocytochemistry. Most cells of the more rostral segments of the primitive streak were found to contribute cells to the endodermal layer, adjacent to precardiac mesodermal cells of the he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 47 publications
1
23
0
Order By: Relevance
“…Explant experiments, primarily done in the chick embryo, have yielded conflicting results on this question (reviewed in (Yutzey and Kirby, 2002)). Whereas some studies argue that cells exist in the early gastrula that are capable of forming cardiomyocytes regardless of later location in the embryo (Auda-Boucher et al, 2000; Lopez-Sanchez et al, 2009), others suggest that ultimate localization to the ALPM is sufficient for cardiac differentiation (Inagaki et al, 1993; Tam et al, 1997). A lack of mutants that specifically affect early myocardial progenitor development, and markers to isolate and characterize these cells, has hindered progress on this key question of early heart development.…”
Section: Introductionmentioning
confidence: 99%
“…Explant experiments, primarily done in the chick embryo, have yielded conflicting results on this question (reviewed in (Yutzey and Kirby, 2002)). Whereas some studies argue that cells exist in the early gastrula that are capable of forming cardiomyocytes regardless of later location in the embryo (Auda-Boucher et al, 2000; Lopez-Sanchez et al, 2009), others suggest that ultimate localization to the ALPM is sufficient for cardiac differentiation (Inagaki et al, 1993; Tam et al, 1997). A lack of mutants that specifically affect early myocardial progenitor development, and markers to isolate and characterize these cells, has hindered progress on this key question of early heart development.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have focused on identifying the embryonic origins of cardiogenic mesoderm in amniotes, particularly chicken and mouse embryos, which, similar to human, develop a four-chambered heart. However, the majority of these studies have involved fate mapping experiments in the chick due to their accessibility and ease of manipulation in ovo and ex ovo which makes them well suited to analyse early cardiac lineage and cell fate [2], [3], [4], [5].…”
Section: Introductionmentioning
confidence: 99%
“…Montgomery et al, 1994;Schoenwolf and Garcia-Martinez, 1995). However, recent work suggests that presumptive cardiac progenitors from the pregastrula embryo do have the potential to form cardiomyocytes when placed in ectopic (normally non-cardiogenic) embryonic locations (Lopez-Sanchez et al, 2009). Studies in mouse and sea squirt Ciona intestinalis have shown that Mesp family basic helix-loop-helix transcription factors are essential for cardiac mesoderm formation (Kitajima et al, 2000;Satou et al, 2004), and indeed Mesps can promote cardiac differentiation of ES cells in vitro (Bondue et al, 2008).…”
Section: Introductionmentioning
confidence: 99%